2014
DOI: 10.1371/currents.outbreaks.9e4c4294ec8ce1adad283172b16bc908
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variations in the Effective Reproduction Number of the 2014 West Africa Ebola Outbreak

Abstract: Background The rapidly evolving 2014 Ebola virus disease (EVD) outbreak in West Africa is the largest documented in history, both in terms of the number of people infected and in the geographic spread. The high morbidity and mortality have inspired response strategies to the outbreak at the individual, regional, and national levels. Methods to provide real-time assessment of changing transmission dynamics are critical to the understanding of how these adaptive intervention measures have affected the spread of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
92
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 15 publications
7
92
1
Order By: Relevance
“…The growing concern over the repeated emergence of EVD (7,8) has stimulated many studies on these outbreaks, in particular on the most recent one in West Africa, trying to understand the transmission mechanisms and the effectiveness of containment strategies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These studies, however, either used limited data at an early stage of the epidemic or assessed a single influential factor.…”
mentioning
confidence: 99%
“…The growing concern over the repeated emergence of EVD (7,8) has stimulated many studies on these outbreaks, in particular on the most recent one in West Africa, trying to understand the transmission mechanisms and the effectiveness of containment strategies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These studies, however, either used limited data at an early stage of the epidemic or assessed a single influential factor.…”
mentioning
confidence: 99%
“…For example, the effectiveness of some control programs, such as the cordon sanitaire implemented in Monrovia, Montserrado County, have been questioned, due to lack of public support, infeasibility, and little evidence of incidence reduction. 6,18 By partitioning the epidemic into a primary and a secondary phase, each with its own reproductive number, our model predicts that the transition points-synonymous with decreases in transmission intensity-occurred around September 6 for the earliest epidemic in Lofa County and around December 4 for the latest epidemic in Grand Cape Mount County. For The county-level transition points calculated in this study are generally consistent with a previous country-level phenomenological analysis in Liberia that found an initial reduction in the reproductive number around the week of September 6 and a secondary drop around the week of October 1.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention strategies like vaccination, isolation or quarantine, treatment, public health educational campaign, use of contraceptives just to mention but a few, will be effective when the disease dynamics is known. Individual strategy may not be successful as observed by Sherry, et al, [19]. In their study, they used the timeseries data for the Ebola virus disease cases to estimate how the rate of exponential rise of new cases had changed over the outbreak and found that in the effective reproduction, number rose when the outbreak spread to densely populated cities, and the enforced quarantine measures were not effective control measures.…”
Section: Metapopulation and Epidemicsmentioning
confidence: 97%